Early Plasma Osmolality Levels and Clinical Outcomes in Children Admitted to the Pediatric Intensive Care Unit: A Single-Center Cohort Study - Wang, Huabin; He, Zhongyuan; Li, Jiahong; Lin, Chao; Li, Huan; Jin, Ping; Chen, Chun (Frontiers in Pediatrics, 2021)
Objective: Identifying high-risk children with a poor prognosis in pediatric intensive care units (PICUs) is critical. The aim of this study was to assess the predictive value of early plasma osmolality levels in determining the clinical outcomes of children in PICUs. Methods: We retrospectively assessed critically ill children in a pediatric intensive care database. The locally weighted-regression scatter-plot smoothing (LOWESS) method was used to explore the approximate relationship between plasma osmolality and in-hospital mortality. Linear spline functions and stepwise expansion models were applied in conjunction with a multivariate logistic regression to further analyze this relationship. A subgroup analysis by age and complications was performed. Results: In total, 5620 pediatric patients were included in this study. An approximately “U”-shaped relationship between plasma osmolality and mortality was detected using LOWESS. In the logistic regression model using a linear spline function, plasma osmolality ≥ 290 mmol/L was significantly associated with in-hospital mortality [odds ratio (OR) 1.020, 95% confidence interval (CI) 1.010-1.031], while plasma osmolality < 290 mmol/L was not significantly associated with in-hospital mortality (OR 0.990, 95% CI 0.966-1.014). In the logistic regression model with plasma osmolality as a tri-categorical variable, only high osmolality was significantly associated with in-hospital mortality (OR 1.90, 95% CI 1.38-2.64), whereas low osmolality was not associated with in-hospital mortality (OR 1.28, 95% CI 0.84-1.94). The interactions between plasma osmolality and age or complications were not significant. Conclusion: High osmolality, rather than low osmolality, can predict a poor prognosis in children in PICUs.